⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ f ( x ) = 1 − x 1 g ( x ) = x 2 − a 2 a h ( x ) = ( f ∘ g ) ( x ) Given the system of functions above, find the value of a such that h ( x ) = x 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Kartik Malik Can u send me ur paper of technothlon ?
Problem Loading...
Note Loading...
Set Loading...
h ( x ) = f ( g ( x ) ) = f ( x 2 − a 2 a ) = 1 − a x 2 − a 2 = 1 + a − a x 2 ∴ 1 + a − a x 2 = x 2 ⇒ 1 + a = x 2 ( 1 + a 1 ) Since we can take any arbitrary value for x , its coefficient must be 0 . ∴ a = − 1